The implications of new censorship theory: Conformity and resistance of subtitle translators in China - Lu Yan (JoSTrans: The Journal of Specialised Translation)
Censorship penetrates the decisions made about multilingual communication in an age defined by technification, digitisation and ‘Internetisation’. Rather than perceiving censorship solely as a repressive action externally exerted on subjects, this article explores its productive nature in the hands of new censorship theory in both official and non-official contexts. At its outset, the article presents the Chinese government’s legal control over the media landscape, casting a shadow over the subtitling industry’s present policies. It then examines three self-censorship practices of subtitle translators, based on in-depth interviews and questionnaires conducted with professional and non-professional subtitle translators in state media, media localisation companies and fan-subtitling teams. Subtitle translators, under the impact of explicit and implicit regulations imposed by state actors and structural mechanisms of control, either conform to or circumvent and challenge these regulations. Productive censorship can shape the knowledge and opinions, foster extensive discussions, inspire innovative translation strategies, create fresh lexicons, and enhance the marketability of audiovisual products to a wider audience.